Correlations between types of culture, styles of communication and forms of interreligious dialogue - Minnema, Lourens (HTS teologiese studies, 2014)
This article argues that culture encodes behavioural and conceptual patterns of dealing with inside–outside boundaries, and that as a consequence, different types of culture are likely to encode different styles of communication and corresponding forms of dialogue. It suggests that dialogical partners may benefit from the insight that interreligious dialogue tends to display patterns related to the underlying mechanisms of intercultural communication and that these cultural mechanisms are more influential in the dialogical process and outcome than the religious ideals pursued. Developmental models of dialogue in particular will be discussed.